Partial renneting of pasteurised bovine milk: Casein micelle size, heat and storage stability. (June 2016) - Sinaga, Hotnida; Bansal, Nidhi; Bhandari, Bhesh
Abstract: The effects of partial renneting at low temperature on the casein micelle (CM) size and the storage stability of milk were investigated. Low chymosin concentrations (≤ 0.03 IMCU mL − 1 ) was applied to pasteurised skim milk at 4 °C and enzyme activity was terminated by thermal application at 60 °C/3 min and 85 °C/30 min, referred to as low heat (LHT) and high heat (HHT) treatment milk, respectively. The addition of rennet with concentrations of 0.01, 0.02 and 0.03 IMCU mL − 1 for 15 min resulted in κ-casein hydrolysis of 10, 20 and 25%, respectively. Moreover, mean CM size of milk was reduced by up to 10 nm. For LHT milk, the renneted micelles appeared to be stable for up to 17 days, especially in response to the application of 0.01 IMCU mL − 1 and at a storage temperature of 4 °C. Severe heating at 85 °C/30 min to inactivate the enzyme caused an increase in CM size. Graphical abstract: Highlights: Partial renneting changes casein micelle size. Chymosin activity can be stopped using heat application. Thermal enzyme inactivation affects the milk storage stability.